Hubungan Paritas Dan Mobilisasi Dini Dengan Percepatan Involusio Pada Ibu Nifas - Mudlikah, Siti (Universitas Muhammadiyah Gresik, 2022)
The recovery process of the reproductive organs after giving birth (uterine involution) can occur immediately after giving birth and last up to 6 weeks. Delayed involution can result in bleeding that endangers the mother's life. The process of uterine involution is influenced by factors such as age, parity, education, occupation, early breastfeeding, early mobilization, and maternal nutritional status. The purpose of this study is to determine the relationship between parity and early mobilization with uterine involution. Research method: This study used an analytical method with a cross-sectional approach. The population consisted of 34 postpartum mothers in a private midwife practice from January to May 2023 in Jatikalang Village, Prambon Subdistrict, Sidoarjo Regency. Total sampling was used for the sample. The instrument used was a questionnaire. Parity and early mobilization data were obtained directly from the questionnaire, while uterine involution data were obtained from the results of palpation examination using a checklist. Data analysis used frequency distribution with a chi-square statistical test with a p-value of ​